2005
DOI: 10.1007/s00125-005-1857-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase dysfunction in diabetic mice: importance of tetrahydrobiopterin in eNOS dimerisation

Abstract: Aims/hypothesis: Impaired nitric oxide (NO) bioactivity and increased superoxide (SO) production are characteristics of vascular endothelial dysfunction in diabetes. The underlying mechanisms remain unknown. In this regard, we investigated the role of tetrahydrobiopterin (BH4) bioavailability in regulating endothelial nitric oxide synthase (eNOS) activity, dimerisation and SO production in streptozotocin-induced diabetic mice. Methods: Mouse aortas were used for assays of the following: (1) aortic function by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 50 publications
7
96
0
Order By: Relevance
“…As described before, the condition of vascular (endothelial) dysfunction in diabetes is associated with a paradoxical increase rather than decrease of a functionally uncoupled eNOS. The increase in eNOS expression has been attributed to the increased formation of the superoxide dismutation product hydrogen peroxide (H 2 O 2 ), which increases eNOS expression at the transcriptional and also translational level [16][17][18]. In our study, treatment of STZ rats with atorvastatin led to a reduction in eNOS expression, which might be explained by the reduction in oxidative stress and the subsequently decreased formation of the eNOS expression stimulus H 2 O 2 .…”
Section: By Which Mechanism Does Atorvastatin Prevent Enos Uncoupling?supporting
confidence: 47%
See 1 more Smart Citation
“…As described before, the condition of vascular (endothelial) dysfunction in diabetes is associated with a paradoxical increase rather than decrease of a functionally uncoupled eNOS. The increase in eNOS expression has been attributed to the increased formation of the superoxide dismutation product hydrogen peroxide (H 2 O 2 ), which increases eNOS expression at the transcriptional and also translational level [16][17][18]. In our study, treatment of STZ rats with atorvastatin led to a reduction in eNOS expression, which might be explained by the reduction in oxidative stress and the subsequently decreased formation of the eNOS expression stimulus H 2 O 2 .…”
Section: By Which Mechanism Does Atorvastatin Prevent Enos Uncoupling?supporting
confidence: 47%
“…For example, statin-induced inhibition of protein-isoprenylation (e.g., of RhoGTPases) can prevent the assembly of the membrane bound NADPH oxidase [12], decrease the amount of membrane bound endothelin-1 receptor [13] and increase eNOS activity [14] and eNOS-mRNA stability [15]. Interestingly, statin therapy as well as diabetes mellitus may lead to increase in eNOS protein expression [16][17][18], which may be beneficial only when the enzyme is in its coupled state. Recently, two groups have demonstrated that HMG-CoA reductase inhibition increases the expression of the GTPCH-I and subsequently cellular BH 4 levels in cultured endothelial cells and that inhibitory effects of high glucose on the GTPCH-I expression as well as the BH 4 lowering effects were reversed by the HMG-CoA reductase inhibitor atorvastatin [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from eNOS expression and phosphorylation, decreased availability of the eNOS substrate L-Arg or cofactors such as BH 4 also occurs in diabetes [38] and has been reported to be significantly lower in diabetic patients [39,40]. In our study, although direct measurements of L-Arg and BH 4 were not performed, incubation with these agents potentiated the relaxation induced by ACh in aorta of sedentary db/db mice.…”
Section: Discussionmentioning
confidence: 51%
“…compromises BH4 levels and promotes the degradation of the active NOS dimer into inactive monomeric subunits (1,16,47), eNOS enzymatic activity was robustly increased. This ability of Nox5 to activate eNOS was shown in a heterologous expression system in COS cells, in cultured endothelial cells, and also in intact blood vessels.…”
Section: Nox5 and Regulation Of Cellular Functionmentioning
confidence: 99%